The Influence of Transfer Price, Capital Intensity and Profitability on Tax Avoidance: An Empirical Study on Consumer Non-Cyclical Sector Companies on the Indonesia Stock Exchange - Depi Aji Purwanto; Hari Stiawan (Journal of Community Service and Rural Development, 2025)
This study aims to analyze the Effect of Transfer Prices, Capital Intensity and Profitability on Tax Avoidance. The population in this study are Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange in 2019-2023. This data collection technique is secondary data with data collection methods, namely literature studies and documentation. The sample collection technique for this study is the purposive sampling method using eviews series 12 software. This study uses samples obtained from 21 Consumer Non-Cyclicals sector companies, the analysis technique used is panel data regression. The research used is a quantitative approach that is associative. The results of this study indicate that Transfer prices have an effect on Tax Avoidance in Consumer Non-Cyclicals Companies listed on the Indonesia Stock Exchange for the 2019-2023 period. Capital Intensity has no effect on Tax Avoidance in Consumer Non-Cyclicals Companies listed on the Indonesia Stock Exchange for the 2019-2023 period. Profitability has an effect on Tax Avoidance in Consumer Non-Cyclical Companies listed on the Indonesia Stock Exchange for the 2019-2023 Period. Capital Intensity and Profitability simultaneously have a significant effect on Tax Avoidance in Consumer Non-Cyclical Companies listed on the Indonesia Stock Exchange for the 2019-2023 Period.